Rome: An Empire of Many Nations New Perspectives on Ethnic Diversity and Cultural Identity - Price, Jonathan J.; Finkelberg, Margalit; Shahar, Yuval (Humanities, 2022)
Explores the nature of the vast multinational Roman Empire through the identities of ethnic groups and the experiences of single individuals. The chapters range across the many cultures, languages, religions and literatures of the Empire, with a special focus on the Jews as a test-case for the larger issues.